Impact of Occupational Safety Compliance on Cost and Duration of Construction Projects in Pakistan - Mujtaba Hassan; Nor Haslinda Abas; Samiullah Sohu; Muhammad Mujtaba Asad (International Journal of Sustainable Construction Engineering and Technology, 2025)
The construction industry significantly contributes to economic stability and employment generation globally. However, persistently high accident rates underscore widespread deficiencies in safety compliance. This study investigates the direct impact of occupational safety compliance on the cost and duration of construction projects. A quantitative research methodology was employed, utilizing a structured survey to collect data from safety compliance practitioners, including clients, consultants, and contractors, across eight large-scale construction projects in Pakistan. Data normality was confirmed, and Pearson correlation analysis was applied to evaluate relationships. The findings reveal a positive correlation between occupational safety compliance and both project duration and overall project cost. These results underscore the importance of integrating safety compliance with effective project management to achieve a balanced approach that enhances worker safety while optimizing project efficiency. This study provides valuable insights for stakeholders aiming to improve safety practices without compromising project objectives, contributing to the broader discourse on safety management in construction.